Managing risks of crowdsourcing innovation: an action research in progress - Souza, Lieda (2009)
Over the last few years, a number of academics and practitioners have emphasized the value of innovation as a main driver for firms to enhance their business performance and sustain a high profitability. Recent studies of innovation have pointed to the growing relevance of external sources of innovation and the firm's necessity of involving a wide range of internal and external actors and sources to help achieving and sustaining its business strategy. The company can become more innovative by implementing a process of cocreation. It can do this in two ways (1) by internally identifying the business problems and needs for innovation felt by individuals, teams and organizational units (seekers) and furthering the emergence of a community of specialists (within or outside the organization), or employees motivated to provide their knowledge and skills to address innovation problems, increasing their internal visibility and ensuring their empowerment across the company (solvers); (2) by placing its innovation problems and needs to a brokering service that can find the right people to present solutions. These two forms of open innovation is called Crowdsourcing Innovation. Innovation brings risks. Risk of Financial loss or of being unsuccessful. If innovation requires business or organizational change, the risk is even bigger because innovation implies newness and unknown. Any company that innovates must face the inherent risks. Facing the risks requires that the company manages them, understanding in advance their nature and impact, monitoring the relevant indicators to anticipate their occurrence, and being ready to act immediately at the first signs of trouble. The innovating company should consider managing risks as one of its core competences. Without this capability, any innovation project can become an opportunity to dramatically fail the business objectives and sustainability. Steady progress has been made over the last years in understanding open innovation strategy. This paper adds to that effort by focusing